RANCANG BANGUN ALAT PENGURAS SELANG UNTUK MENCEGAH KERUSAKAN - Muhammad Taufiqul Kamil; Rahmawati Sukra; Nunuk Praptiningsih (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
This study discusses the design and development of a Drain Hose Equipment to improve the maintenance of fire hoses in the Aircraft Rescue and Fire Fighting (ARFF) unit at Politeknik Penerbangan Indonesia Curug. The equipment addresses the limitations of manual draining methods, which often leave residual water inside hoses, leading to mold, corrosion, and reduced service life. By applying a gravity roller system integrated with a trolley, the tool efficiently removes remaining water without requiring external power. This research adopts the Research and Development (R&D) method, starting from observation to product validation. The results indicate increased efficiency, reduced labor effort, and faster operational readiness. Although the equipment performs well, further refinement is needed for uneven field conditions. This innovation contributes to safer and more sustainable equipment maintenance and may be applicable to other emergency response industries.